OVERVIEW OF THE LEVEL OF KNOWLEDGE, ATTITUDES, AND BEHAVIORS OF MOISTURISER USE IN STUDENTS - Toar T. J. Rawung; Marlyn G. Kapantow; Ferra O. Mawu (Riviera Publishing, 2025)
Skin care is essential for health and appearance, particularly among students. The skin, as the largest organ, protects the body from external threats; however, in North Sulawesi, the tropical climate can lead to issues such as dry skin. Dry skin affects approximately 3% of adolescents and up to 85% of individuals aged 35-44, potentially resulting in infections and depression. Although moisturizers are a common solution for this issue, many medical students lack understanding of their importance, which can negatively impact their skin health. To assess the level of knowledge, attitude, and behavior regarding moisturizer use among students of the Medical Education Program at Sam Ratulangi University. This study employs a descriptive design with a cross-sectional approach. Sampling was conducted through total purposive sampling. Primary data collected were analyzed univariately using various statistical programs. The level of knowledge regarding moisturizer use was categorized as sufficient (77.84%), the attitude towards moisturizer use was categorized as good (89.17%), and the behavior regarding moisturizer use was categorized as sufficient (71.70%). The depiction of knowledge, attitude, and behavior regarding moisturizer use among students of the Medical Education Program at Sam Ratulangi University falls into the sufficient category.